Evidence-Based Practice Recommendations for Hydration in Children and Adolescents With Cancer Receiving Intravenous Cyclophosphamide. (July 2014) - Robinson, Deborah; Schulz, Ginny; Langley, Rachel; Donze, Kevin; Winchester, Kari; Rodgers, Cheryl
Hemorrhagic cystitis is a known complication of cyclophosphamide, an antineoplastic agent used to treat a variety of oncologic diseases in children. Hydration can prevent hemorrhagic cystitis; however, use varies in clinical practice. A team was assembled to develop evidence-based practice recommendations to address the following question: in a population of children with cancer, what is the appropriate pre- and posthydration for the administration of different dose levels of intravenous cyclophosphamide to prevent bladder toxicity? The purpose was to identify the appropriate rate, duration, and route of hydration to prevent bladder toxicity with low, intermediate, and high dose cyclophosphamide. After a systematic search of the literature, 15 pieces of evidence were evaluated and used. There is a moderate level of quality evidence related to hydration for high dose cyclophosphamide and very low quality evidence related to intermediate or low dose cyclophosphamide. Three general recommendations were made for hydration associated with cyclophosphamide. There is a need for further research related to the prevention of bladder toxicity in children with cancer receiving cyclophosphamide.